High-Yield Alpha-Cellulose from Oil Palm Empty Fruit Bunches by Optimizing Thermochemical Delignification Processes for Use as Microcrystalline Cellulose - Susi, Susi; Ainuri, Makhmudun; Wagiman, Wagiman; Falah, Mohammad Affan Fajar (International Journal of Biomaterials, 2023)
Oil palm empty fruit bunches (OPEFB) are lignocellulosic materials that are a by-product of the palm oil industry, which have less use and utilization is still limited. OPEFB’s high cellulose content could potentially develop into various bioproducts, especially biomaterials. The thermochemical delignification process can obtain high-yieldalpha-cellulose. The cellulose extraction process can be done by combining the bleaching process under acidic conditions and alkaline delignification to obtain high-purity cellulose. The bleaching conditions vary in the concentration of NaClO2, the length of bleaching, the temperature, and the number of stages. The research obtains high α-cellulose by optimizing bleaching conditions under acidic conditions in cellulose’s OPEFB extraction with variability on NaClO2 concentration and bleaching time using response surface methodology (RSM). The bleaching process was implemented at an early stage with a concentration of 3% NaClO2 and a bleaching time of 2 hours as a center point with a bleaching cycle of twice at pH 4–4.5 using acetic acid. Bleached fibers were delignified using 10% NaOH for 2 hours at room temperature. The RSM analysis resulted in optimum bleaching conditions at a concentration of 3.22% NaClO2 for 1 hour, yielding OPEFB’s cellulose of 82.96% ± 2.53, hemicellulose of 9.27% ± 2.28, and lignin of 1.68% ± 0.58. The validation and verification process in the bleaching conditions obtained cellulose of 84.87% and α-cellulose of 88.51%, with a crystallinity index of 70.55% and crystallite size of 2.35 nm. Scanning electron microscopy on surface cellulose morphology at optimum bleaching helped remove hemicellulose impurities, lignin, and inorganic materials and a more intensive opening of cellulose fibrils. The bleaching process optimization point was verified to improve the delignification performance and potentially produce high yield α-cellulose content for microcrystalline cellulose use.